Learning Environment of Science in Junior High School Which Use Curriculum 2013 in Baturetno Wonogiri - Bowo Sugiharto; Baskoro Adi Prayitno, Sri Widoretno (Universitas Sebelas Maret, 2015)
This research aims to describe the science learning environment in junior high school which use curriculum 2013 in Baturetno Wonogiri. The research was descriptive qualitative research. The subject of research was SMPN 1 Baturetno Wonogiri. The data of learning environment obtained through observation of lessons learned in class and specializes in relationship dimension. The data was analyzed in descriptive qualitative. The research shows that science learning environment especially seen from the relationship dimensions there were two sides i.e the interaction between students and student and the interaction between students and teacher. The interaction between students and students showed that it is the class is quite calm and not indicate the presence of noise but the cooperation each other still need to develop. The Interaction between students and teacher tend shows a conventional teaching and learning patern (teacher centered), not empowering the students to build a collaborative culture. Thus it can be concluded that the learning environemnt of science subject in SMPN 1 Baturetno need to optimalized.Keywords:learning environment, science teaching and learning